Residual stress in laser bent steel components - Topić, M; Bucher, R; Vorster, W; Zhang, S; McGrath, P; Korsunsky, A (Trans Tech Publications, 2006)
The kinetics of plastic deformation and microstructural evolution, and the residual stress in particular, were investigated on the steel plates (SABS 1431) bent by laser beam. The steel plates were bent by different number of laser scans and therefore, each was bent to a different extent. The stress results obtained by x-ray diffraction (sin²φ-method) show a higher compressive stress along the laser path than in the transverse direction. It was also found that stress relaxation occurs during multi-scan laser forming process and most importantly, that the stress is not significantly different in comparison to the stress, which initially existed in rolled steel plates. The metallographic analyses show that phase transformation, dynamic recovery and recrystallization processes occur during laser forming.